1987
DOI: 10.1177/016555158701300504
|View full text |Cite
|
Sign up to set email alerts
|

Scientists and information work: the careers of the 1979-1985 MSc graduates from the Department of Information Studies, University of Sheffield

Abstract: This paper reports the results of a postal survey (91% response) of students from the Department of Information Studies, University of Sheffield who were awarded the MSc in Information Studies between 1979 and 1985, inclusive. Re-spondents were asked about their careers and to evaluate the MSc programme. A high proportion (49% if only UK students are included or 44% if overseas students are also included) of the graduates entered industry and commerce as their first destination and only 1% of UK students were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…This compared well with responses rates of previous studies (84.7% Roberts and Bull [10], 83%, 93%, 91% Wood [13,14,15].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This compared well with responses rates of previous studies (84.7% Roberts and Bull [10], 83%, 93%, 91% Wood [13,14,15].…”
Section: Resultssupporting
confidence: 90%
“…However, many of the points below are supported by the companion survey of former students of the MSc in Information Studies programme reported by Wood [15].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Students on the MA librarianship course in the 1980s generally found employment in academic and public libraries (Loughridge and Sutton, 1988): while the numbers going into such traditional roles decreased steadily, falling from 77 per cent in the late 1970s to just under 50 per cent in the early 1990s, this was compensated for by substantial growth in special-library and information-management positions (Loughridge et al, 1996). Of the two MSc programmes, students on the MA information studies (social sciences) were evenly split between jobs in librarianship and other information work by the early 1980s (Roberts and Bull, 1983); almost half of the MSc information studies graduates at that time had entered industry and commerce and almost one-third were working in predominantly IT positions (Wood et al, 1987). A subsequent survey in the 1990s found that graduates from the merged MSc information management course continued to work predominantly in industry and commerce (Quarmby et al, 1999).…”
Section: Student Careersmentioning
confidence: 99%
“…A later report of a survey covering the careers of graduates of the MSc in Information Studies in the years 1979 to 1985 did, however, include a section on evaluation of the programme (Wood et al, 1987). As Wood records, a major restructuring of the programme had been carried through in 1981 and 1982 and only the views of graduates who had taken the MSc since its last major revision were included in this section.…”
Section: Relevance and Value Of The Programmesmentioning
confidence: 99%